2018
DOI: 10.1007/s10646-018-1933-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and trends in lead (Pb) concentrations in bald eagle (Haliaeetus leucocephalus) nestlings from the western Great Lakes region

Abstract: Most studies examining bald eagle (Haliaeetus leucocephalus) exposure to lead (Pb) have focused on adults that ingested spent Pb ammunition during the fall hunting season, often at clinical or lethal levels. We sampled live bald eagle nestlings along waterbodies to quantify Pb concentrations in 3 national park units and 2 nearby study areas in the western Great Lakes region. We collected 367 bald eagle nestling feather samples over 8 years during spring 2006-2015 and 188 whole blood samples over 4 years during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
2
6
0
Order By: Relevance
“…A very high proportion (95%) of nestlings we tested had been exposed to lead. Although this rate is higher than that reported for other raptors (Harmata 2011; Katzner et al 2017; Bruggeman et al 2018; Herring et al 2020), that most exposure was at a low level is consistent with findings for other raptors (Carlson et al 2012). Nestling raptors can be exposed to lead from inhalation, ingestion, or maternal transfer (Pattee 1984; Katzner et al 2017; Bruggeman et al 2018).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A very high proportion (95%) of nestlings we tested had been exposed to lead. Although this rate is higher than that reported for other raptors (Harmata 2011; Katzner et al 2017; Bruggeman et al 2018; Herring et al 2020), that most exposure was at a low level is consistent with findings for other raptors (Carlson et al 2012). Nestling raptors can be exposed to lead from inhalation, ingestion, or maternal transfer (Pattee 1984; Katzner et al 2017; Bruggeman et al 2018).…”
Section: Discussionsupporting
confidence: 85%
“…Although this rate is higher than that reported for other raptors (Harmata 2011; Katzner et al 2017; Bruggeman et al 2018; Herring et al 2020), that most exposure was at a low level is consistent with findings for other raptors (Carlson et al 2012). Nestling raptors can be exposed to lead from inhalation, ingestion, or maternal transfer (Pattee 1984; Katzner et al 2017; Bruggeman et al 2018). Wedge‐tailed eagles, like other raptors, are thought to mainly provision their nestlings with live‐caught prey (Olsen 2005); however, exposure through consumption is still possible due to prey species surviving being shot and containing lead ammunition (Pain et al 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Wildlife populations face mounting threats to long‐term viability from anthropogenic activities. Among these threats are environmental contaminants that can reduce overall population potential (Pain et al 2009, Franson and Russell 2014, Bruggeman et al 2018). While not directly lethal, a prime example is the contaminant dichlorodiphenyltrichloroethane (DDT), which severely affected wildlife populations across the United States.…”
mentioning
confidence: 99%
“…Despite the Eagle Act rendering the direct take of a bald eagle illegal in the United States (USFWS 1940), veterinary records from necropsies on bald eagles collected in the wild by state wildlife agency biologists and their partners show that ingestion of discarded tissues containing spent Pb ammunition fragments is a widespread source of morbidity and mortality to eagles (Katzner et al 2018). Ingestion of Pb fragments by wild scavenging eagles can cause acute or chronic morbidity and mortality, dependent on the quantity of Pb ingested in the contaminated tissues of the scavenged meal (Stansley and Murphy 2011, Franson and Russell 2014, Bruggeman et al 2018). Despite the steady increase in eagle abundances in the northeast United States in recent years (USFWS 2007, Hanley et al 2019), wildlife rehabilitators, veterinarians, and pathologists in the northeast United States continue to report eagle morbidities and mortalities from ingested Pb (Avian Haven Wild Bird Rehabilitation Center 2021, Cummings School of Veterinary Medicine 2021, University of New Hampshire 2021, USGS National Wildlife Health Center 2021, Wildlife Health Center of Virginia 2021), spawning regional and national controversy among wildlife managers, resource regulators, and the public on whether Pb ammunition should be banned outright (USDOI 2017 a , b ).…”
mentioning
confidence: 99%
“…Primary food items for both bald and golden eagles include live fish, birds, or mammals, and both eagle species opportunistically feed on carrion. Thus, each species may be exposed to lead through the ingestion of spent ammunition in discarded entrails or carcasses of hunter‐harvested animals (Hunt et al 2006, Franson and Russell 2014, Lindblom et al 2017) or lead lures or sinkers attached to fish consumed by eagles (Bruggeman et al 2018). Previous studies found that detectable concentrations of lead are common in wild bald and golden eagle populations (Stauber et al 2010, Harmata and Restani 2013, Warner et al 2014), wherein blood lead concentrations were elevated in 50–60% of the bald eagles and 42–56% of golden eagles surveyed.…”
mentioning
confidence: 99%